Il Fast-Track delle fratture di femore prossimale over 65: la realtà ospedaliera italiana - Cudoni, S.; Zedde, P. (Lo Scalpello - Journal, 2018)
THE FAST-TRACK OF PROXIMAL FEMORAL FRACTURES IN THE PATIENT OVER 65: THE ITALIAN HOSPITAL REALITYFractures of the femoral neck in over-65 patients are today a topical subject owing to both their significant clinical andeconomic impact and their ever-increasing incidence. The growing and widespread adherence of the Italian NationalHealthcare System to the treatment of these fractures within 24–48 hours has allowed over the last few years to reducethe number of complications and the medium to long-term mortality rate associated with this important social andeconomic problem.